2017
DOI: 10.1016/j.worlddev.2017.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Land Tenure Security and Household Human Capital: Evidence from Ethiopia’s Land Certification

Abstract: This paper examines the impact of Ethiopia’s gendered land certification programs on household consumption of healthcare, food, education, and clothing. Ethiopia embarked on a land tenure reform program in 1998, after years of communism during which all land was nationalized. The reform began in Tigray region where land certificates were issued to household heads, who were primarily male. In a second phase carried out in 2003–2005, three other regions issued land certificates jointly to household heads and spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…One study reported associations between equity in land and food expenditure, showing no differences in food expenditure between households where land was held jointly by men and women in Ethiopia, compared with head-only land certification. 41 Two studies reported associations between equity in land and household dietary diversity, showing mixed results. In India, women's name on land title (compared with men's) was not associated with household dietary diversity.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported associations between equity in land and food expenditure, showing no differences in food expenditure between households where land was held jointly by men and women in Ethiopia, compared with head-only land certification. 41 Two studies reported associations between equity in land and household dietary diversity, showing mixed results. In India, women's name on land title (compared with men's) was not associated with household dietary diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Women heads of households were generally reduced to sharecropping [38]. The First Stage Land Registration (FSLR), initiated in 1998-1999 in Tigray, enabled female household heads to obtain certificates in their name, but failed to provide for spouses in MHHs [36,39,40]. The Second Stage Land Registry (SSLR) i 2003 allowed spouses to receive land certificates in their name [40].…”
Section: Gendered Access To Resources: Land Labor and Finance In Rumentioning
confidence: 99%
“…The First Stage Land Registration (FSLR), initiated in 1998-1999 in Tigray, enabled female household heads to obtain certificates in their name, but failed to provide for spouses in MHHs [36,39,40]. The Second Stage Land Registry (SSLR) i 2003 allowed spouses to receive land certificates in their name [40]. According to Holden and Tilahun [39], 90% of FHHs hold land, 45% of women in MHHs do not hold a land certificate, and in 35% of MHHs, land is certified jointly.…”
Section: Gendered Access To Resources: Land Labor and Finance In Rumentioning
confidence: 99%
“…Even if girls are not given land to own, sensitization could also be used to encourage all families to avail land for growth of food or rearing animals by young mothers since women are the main providers of agricultural labor in Africa [41,42]. A study in Ethiopia reported that a certified family ownership of land was demonstrated to be effective in helping women to own land and use it for economic growth [43], a case that could be borrowed for advocacy to help young mothers in rural Uganda to own land too.…”
Section: Discussionmentioning
confidence: 99%